2019
DOI: 10.1186/s12985-019-1218-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to rescue and culture duck Astrovirus type 1 in vitro

Abstract: Background Reverse genetics systems enable the manipulation of viral genomes and therefore serve as robust reverse genetic tools to study RNA viruses. A DNA-launched rescue system initiates the transcription of viral genomic cDNA from eukaryotic promoter in transfected cells, generating homogenous RNA transcripts in vitro and thus enhancing virus rescue efficiency. As one of the hazardous pathogens to ducklings, the current knowledge of the pathogenesis of duck astrovirus type 1 (DAstV-1) is limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The epitope motif identified in this study was conserved among all the DAstV-1 strains, but was obviously different from the strains of DAstV-2, DAstV-3, and DAstV-4 ( Figure 6). To date, only DAstV-1 can be cultured and passaged in cells [28], while other serotypes of DAstV can only be passaged by ducklings [15][16][17]. Reactivity analysis showed that the mAb 3D2 could only react with the epitope 454 STTESA 459 in DAstV-1 ORF2, while not with 454 GDWQSN 459 in DAstV-2 ORF2, 454 DSWKSH 459 in DAstV-3 ORF2, and 454 TNWNGN 459 in DAstV-4 ORF2 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The epitope motif identified in this study was conserved among all the DAstV-1 strains, but was obviously different from the strains of DAstV-2, DAstV-3, and DAstV-4 ( Figure 6). To date, only DAstV-1 can be cultured and passaged in cells [28], while other serotypes of DAstV can only be passaged by ducklings [15][16][17]. Reactivity analysis showed that the mAb 3D2 could only react with the epitope 454 STTESA 459 in DAstV-1 ORF2, while not with 454 GDWQSN 459 in DAstV-2 ORF2, 454 DSWKSH 459 in DAstV-3 ORF2, and 454 TNWNGN 459 in DAstV-4 ORF2 (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…DAstV-1 virulent strain D51 (GenBank accession no. MH712856) was isolated from the liver of sick cherry valley ducks in the Shandong province of China in 2012 [28]. The ORF2 gene of DAstV-1 D51 strain was cloned into the prokaryotic expression vectors pET-32a (+) (Novagen, Darmstadt, Germany) and pGEX-6p-1 (GE Healthcare, Amersham, UK) to generate recombinant histidines tagged ORF2 (His-ORF2) and glutathione S-transferase tagged ORF2 (GST-ORF2).…”
Section: Viruses Cells and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One organ system that raises further questions is the detection of astroviruses from tissues of the cardiovascular system. In a small number of studies, astrovirus RNA has been detected in infected human and animal hearts, including pigs, ducks, chickens, and geese [ 19 , 66 , 142 , 143 , 144 ]. In addition, histological findings of myocarditis or epicarditis were identified from two pigs infected with porcine astrovirus [ 66 ].…”
Section: New Frontiers Of Astrovirus Tissue Tropisms and Diseasesmentioning
confidence: 99%
“…Similarly, it is unknown whether astroviruses can infect cells of the immune or hematological systems. Astroviruses have been detected by PCR from splenic tissue, and, in some cases, viral protein has been detected by immunofluorescence in specimens from the spleen [ 51 , 53 , 82 , 143 ]. In addition, the detection of astroviruses in stool has been associated with an increased risk of immune thrombocytopenia in children [ 145 ].…”
Section: New Frontiers Of Astrovirus Tissue Tropisms and Diseasesmentioning
confidence: 99%